Research on Capacity and Distribution Planning of Electric Hydrogen Production Considering Static Voltage Stability Margin - Changsheng HU; Zhijun BAI; Zhang ZHANG; Jiankang LI; Ziyang SHEN (Zhongguo dianli)
With the large-scale grid connection of electric hydrogen production load and the frequent changes of power grid operation mode, the access mode and distribution location of electric hydrogen production equipment cluster have an increasingly significant impact on the stability of power grid. Therefore, this paper proposes a planning method of electric hydrogen production capacity and distribution location considering static voltage stability margin constraints. Firstly, based on the steady-state model of alkaline electrolytic cell, its operating characteristics are analyzed, and the grid-connected mode of transformerless direct-hanging electrolytic cell is constructed. The internal current of hydrogen production system is involved in the Newton-Raphson method iteration of continuous power flow calculation, and the static voltage stability margin of the current system is obtained from the PV curve. Based on the net present value evaluation index, the economic analysis model of the whole life cycle of the hydrogen production system is established. Based on the constraint of static voltage stability margin and the goal of maximizing the net present value of the system, a capacity planning model for the hydrogen production system of the electrolytic cell is proposed. The decision variable is the total capacity of the electrolytic cell. Based on the evaluation index of power transmission distribution factor, the layout planning model of the electrolytic cell at the key nodes of the system is constructed, and the weight of each node is calculated to obtain the capacity configuration result of the electrolytic cell hydrogen production system. Finally, the IEEE 39 node system is used for example analysis. The results show that the proposed method ensures the grid-connected stability of large-scale electric hydrogen production load while taking into account the economy, effectively consumes the redundant configuration of the system and balances the power flow distribution.